Efektivitas rehabilitasi medik terhadap fungsi motorik penderita pasca stroke iskemik - Daulima, Shaula Vaganza; Safei, Imran; Hidayati, Prema Hapsari; Rachman, Mochammad Erwin; Mubarak, Andi Firman (Holistik Jurnal Kesehatan, 2025)
Background: Stroke is a leading cause of death and disability globally, with a significant prevalence in Indonesia. It occurs due to atherosclerosis or heart disease and has significant physical and psychological impacts, including hemiparesis, impaired balance, and impaired motor function. Medical rehabilitation is a crucial part of post stroke recovery to reduce disability and improve patients quality of life. Purpose: Analyzing the effectiveness of medical rehabilitation on motor function in post ischemic stroke patients. Method: This observational analytical study used a cross sectional design with a retrospective approach. The population in this study were ischemic stroke patients undergoing medical rehabilitation at Ibnu Sina General Teaching Hospital, Panakkukang District, South Sulawesi Province, conducted from August to November 2024 with a sample size of 32 patients. Bivariate analysis used the Wilcoxon signed rank test by comparing motor function values before and after physiotherapy. Significance was determined at p ≤ 0.05. Results: The majority of patients were male at 62.5%, patients under 65 years old were 68.8% and patients with right hemiparesis were 59.4%, there was no direct relationship between the frequency of visits and the increase in motor function or MMT of patients undergoing medical rehabilitation, there was an influence of medical rehabilitation carried out for 6 months on the MMT value or motor function of patients. It was found that medical rehabilitation was effective at 33.63% in post-ischemic stroke patients in the first month to the sixth month of rehabilitation. Conclusion: Six months of medical rehabilitation effectively improved motor function by 33.63% in post-ischemic stroke patients, although no direct correlation was found between the frequency of visits and increased MMT scores. The majority of patients undergoing rehabilitation were male, under 65 years of age, and had right hemiparesis.   Keywords: Ischemic Stroke; Medical Rehabilitation; Motor Function.   Pendahuluan: Stroke merupakan salah satu penyebab utama kematian dan disabilitas global dengan angka prevalensi yang signifikan di Indonesia, terjadi akibat aterosklerosis atau penyakit jantung, menimbulkan dampak fisik dan psikologis yang besar, termasuk hemiparesis, gangguan keseimbangan, dan fungsi motorik. Rehabilitasi medik menjadi bagian penting dalam pemulihan pasca-stroke untuk mengurangi disabilitas dan meningkatkan kualitas hidup pasien. Tujuan: Untuk menganalisis efektivitas rehabilitasi medik terhadap fungsi motorik penderita pasca stroke iskemik. Metode: Penelitian observasional analitik desain cross-sectional pendekatan retrospektif. Populasi dalam penelitian ini adalah penderita stroke iskemik yang melakukan rehabilitasi medik di Rumah Sakit Umum Pendidikan Ibnu Sina, Kecamatan Panakkukang, Provinsi Sulawesi Selatan, dilakukan pada bulan Agustus – November 2024 dengan jumlah sampel sebanyak 32 pasien. Analisis bivariat menggunakan uji Wilcoxon signed rank dengan membandingkan nilai fungsi motorik sebelum dan sesudah dilakukannya fisioterapi. Signifikansi ditentukan pada p ≤ 0.05. Hasil: Mayoritas pasien berjenis kelamin laki-laki sebesar 62.5% pasien yang berumur dibawah 65 tahun yaitu 68.8% dan pasien dengan hemiparesis dextra sebesar 59.4%, tidak adanya hubungan langsung antara frekuensi kedatangan dengan kenaikan fungsi motorik atau MMT pasien yang menjalani rehabilitasi medik, adanya pengaruh rehabilitasi medik yang dilakukan selama 6 bulan terhadap  nilai MMT atau fungsi motorik  pasien. Didapatkan bahwa rehabilitasi medik efektif sebesar 33.63% pada pasien pasca stroke iskemik di bulan pertama hingga bulan keenam rehabilitasi. Simpulan: Rehabilitasi medik selama enam bulan efektif meningkatkan fungsi motorik sebesar 33.63% pada pasien pasca stroke iskemik, meskipun tidak ditemukan hubungan langsung antara frekuensi kedatangan dan peningkatan nilai MMT. Mayoritas pasien yang menjalani rehabilitasi berjenis kelamin laki-laki, berusia di bawah 65 tahun, dan mengalami hemiparesis dextra.   Kata Kunci: Fungsi Motorik; Rehabilitasi Medik; Stroke Iskemik.